ANALISIS FAKTOR PENYEBAB GAGAL BAYAR OBLIGASI SYARIAH SUKUK IJARAH PT BERLIAN LAJU TANKER - Handoyo Widyanto (Majalah Ilmiah Bahari Jogja, 2018)
This study examines the sharia bonds of sukuk ijarah. The problem in this study is the factors causing default of sukuk ijarah at Berlian Laju Tanker, Ltd. This research is quantitative descriptive. The data studied in this research is secondary data. The technique used is the method of documentation with quantitative descriptive analysis method. The study found that factors causing default of sukuk ijarah Berlian Laju Tanker, Ltd. are: 1) Breaking the principle of profit sharing into fixed interest; The company establishes a system for profit provided is a fixed interest rate of 10% per annum payable quarterly (3 months). Giving profit in the form of fixed interest is a violation of sharia principles, especially the prohibition of usury usage. 2) The use of sukuk ijarah to repay the debt; In the Prospectus of Berlian Laju Tanker, Ltd. 2007 stated that the proceeds of the bonds will be used to repay the company's debt. This makes the sukuk ijarah funds received become unproductive, whereas the interest to be paid is large enough, resulting the company is unable to meet its obligations (default).